Evaluation of Acute and Subacute Toxicity of Two Different Extracts from Que Zui Tea in Rats. Issue 2 (3rd April 2021) - Wang, Yongpeng; Njateng, Guy Sedar Singor; Zhao, Tianrui; Yang, Meilian; Wang, Yifen; Cao, Jianxin; Liu, Yaping; Cheng, Guiguang
Abstract : The buds of Vaccinium dunalianum Wight (VD) are widely used in Yunnan as herbal tea [Que Zui Tea (QT)] and herb. However, the security and toxicity of QT have not been determined yet. The aim of this study is to evaluate the acute and subacute‐toxicity of hot water (QTW) and aqueous‐ethanol (QTE) extracts of QT. Acute‐toxicity studies of QTW and QTE revealed no signs of related to treatment, indicating that median‐lethal‐dose (LD50 ) values of QTW and QTE is surpass 5000 mg/kg. The results of subacute‐toxicity studies of QTW and QTE showed no significant side reaction of all doses the two extracts. The levels of Lymphocyte (LYM) and percentage of lymphocytes (LYM%) significantly decreased, and percentage of granulocytes (GRA%) increased in rats that received these two extracts at doses greater than 1250 mg/kg/day. However, the 1250 and 2500 mg/kg/day QTW and QTE did not trigger any pathological changes in body weight or organ tissue, so partial changes in blood parameters were considered as minor symptoms. Therefore, the present results demonstrated that the two extracts are safe at 2500 mg/kg/day or at lower doses. GRAPHICAL ABSTRACT: